Origins of legislative policy - Dr. Shorouk Jaber Habib (The college of law and political science journal, 2024)
This research addresses the issue of legislative policy, which is considered the pivot of the legislative process because it represents an interactive legal process that takes place between legislative decision makers in light of the requirements and needs of the people, so that those interests and needs are poured into textual legal templates in a strict legal style characterized by ingenuity and mastery in formulating ideas in a concise manner within Legal frameworks that can be applied if they govern the emerging political, economic and social facts and events in society, and then control and define the ideas on which the law is based within a specific philosophy and vision for the authorities responsible for preparing it within a specific time perspective to ensure the stability of the state’s legal system and not to be confused or conflicted and to achieve the interests of the people.